The prospects for improving public transport in Auckland : a thesis presented in partial fulfillment of the requirements for the degree of Master of Resource and Environmental Planning in 132.899 thesis MRP at Massey University, Manawatu campus, New Zealand - Matthews, Lee Margaret (Massey University, 2011)
In many cities of the World, transport systems continue to focus on private vehicle travel, to the detriment of public transport use. This inclination towards providing for private vehicle travel then makes it difficult to effectively improve public transport systems. This thesis has sought to investigate this transport trend further, exploring the factors integral to public transport success. In working towards this, focus has been placed on addressing the public transport system itself by investigating the service provision elements of public transport. In working towards this, network planning was used to examine how the public transport system itself holds the key to its own success. By undertaking an in-depth analysis into the Auckland public transport network, it was shown that when applied, network planning has the potential to improve the existing public transport system.
Keywords: Network planning; Urban public transport; Resource and environmental planning; Auckland; New Zealand